Analytical study on shear strength of macro synthetic fiber reinforced concrete beams. (1st October 2015) - Yazdanbakhsh, Ardavan; Altoubat, Salah; Rieder, Klaus-Alexander
Highlights: Effect of synthetic macrofibers on the shear capacity of RC beams was studied. Models for predicting the shear capacity of SFRC beams were reviewed. The model predictions were compared with results of testing SNFRC beams. A regression analysis method was used for model calibration. Abstract: Many research investigations have been performed in the past to measure and model the shear capacity of longitudinally reinforced concrete beams incorporating steel fibers (SFRC beams). Unlike SFRC, experimental and analytical studies on reinforced concrete beams with macro synthetic fibers have been limited. In this study the shear strength results from testing 23 full-scale reinforced concrete beams with macro synthetic fibers (SNFRC) are used to assess the predictions and applicability of 11 analytical shear models originally developed for SFRC beams. The results indicate that the analytical models of the fib-MC2010, RILEM, Swamy et al., Mansur et al., and Ashour et al. (Zsutty's) predict the shear strength of SNFRC beams with high accuracy. The fib-MC2010 model predicted the shear strength of slender SNFRC beams accurately, but is conservative for short SNFRC beams. The RILEM model was more conservative than the fib-MC2010 in predicting the shear strength of SNFRC beams. A statistical method was used to calibrate the original RILEM model using a set of SFRC and SNFRC test results.